Determinants of entrepreneurial intention among student using structural equations model. - Abu Bakar , Hatinah; Baistaman , Julaina; Wan Mustapha , Wan Masnieza; Mat Nawi , Farahiyah Akmal (International Journal of Accounting, Finance and Business, 2025)
Entrepreneurial intention among students is crucial for fostering innovation, economic growth, job creation and poverty mitigation. This research was conducted to empirically test the relationship between attitude, subjective norm, risk taking on entrepreneurial intentions among students. The respondents in the study were 205 students from UiTM Kelantan Branch. This study employed purposive sampling. Participants are chosen for experience related to the subject of entrepreneurship. This study used Smart Partial Least Square (SmartPLS) software to analyse the data. This study discovered personal attitude and risk taking have a positive and significant effect on entrepreneurial intentions, while subjective norm has not significant effect on entrepreneurial intentions. The finding may not represent the whole population of undergraduate students in Malaysia. Further research may consider other public and private universities.